2016
DOI: 10.1080/21513732.2016.1237383
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying model uncertainty to improve watershed-level ecosystem service quantification: a global sensitivity analysis of the RUSLE

Abstract: Ecosystem service-support tools are commonly used to guide natural resource management. Often, empirically based models are preferred due to low data requirements, simplicity and clarity. Yet, uncertainty produced by local context or parameter estimation remains poorly quantified and documented. We assessed model uncertainty of the Revised Universal Soil Loss Equation -RUSLE developed mainly from US data. RUSLE is the most commonly applied model to assess watershed-level soil loss. We performed a global sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…In favour of emphasising V-factor estimation is the remark of Garcia-Ruiz (2010) that “among the factors explaining the intensity of soil erosion, plant cover and land uses are considered the most important, exceeding the influence of rainfall intensity and slope gradient”. Moreover, Estrada-Carmona et al (2017) argue that C-factor produces the greatest degree of variation in RUSLE-based predictions and this factor can be improved with the application of better land management practices and agro-environmental friendly measures ( Borrelli et al, 2016 ). It is expected that broad availability of high resolution Sentinel-2 multispectral imagery by ESA, will soon allow replacement of the currently used low resolution FCover layers.…”
Section: Discussionmentioning
confidence: 99%
“…In favour of emphasising V-factor estimation is the remark of Garcia-Ruiz (2010) that “among the factors explaining the intensity of soil erosion, plant cover and land uses are considered the most important, exceeding the influence of rainfall intensity and slope gradient”. Moreover, Estrada-Carmona et al (2017) argue that C-factor produces the greatest degree of variation in RUSLE-based predictions and this factor can be improved with the application of better land management practices and agro-environmental friendly measures ( Borrelli et al, 2016 ). It is expected that broad availability of high resolution Sentinel-2 multispectral imagery by ESA, will soon allow replacement of the currently used low resolution FCover layers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on nine nationwide soil loss data sets, including soil loss estimates for Europe (Panagos et al, 2015e), and the original USLE data set for the USA, Estrada-Carmona et al (2017) performed global sensi-tivity analysis to identify the dominant USLE input factors. For all nine countries Estrada-Carmona et al (2017) found that the C factor and the LS factor were the most influential USLE inputs. Bosco et al (2015) proposed a multi RUSLE model approach to account for the uncertainties in their soil loss estimates and therefore involve the impact of the different representations of the USLE inputs on soil loss estimation.…”
Section: Introductionmentioning
confidence: 94%
“…Such a large difference in the SDR does, however, not necessarily reflect the differences in soil erosion rates. Evans (1995) and Boardman (2006) point out that soil losses derived in plot-scale experiments do not reflect erosion taking place on the landscape scale. Evans (1995) found that plot-scale soil losses are larger than soil losses in the landscape by a factor of 2 to 10 under comparable conditions.…”
Section: Usle Input Realizations -Ranges Plausibility and Their Commentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Studies that have used backward or inverse uncertainty propagation in which modeled and observed values of SE are compared to evaluate model biases, check model's suitability for a basin, and estimate model parameters (Risse et al, 1993;Falk et al, 2010 andCarmona et al, 2017). The backward uncertainty analysis requires observed values of SE, and hence not applicable for ungauged basins.…”
mentioning
confidence: 99%